Abundance and biomass of macrobenthic organisms collected from van Veen grab samples taken in the Beaufort Sea in 2010 - Archambault, Philippe; Dannheim, Jennifer; Piepenburg, Dieter (In: Piepenburg, Dieter; Brey, Thomas; Teschke, Katharina; Dannheim, Jennifer; Kloss, Paul; Hansen, Miriam Lea Sarah; Kraan, Casper (2023): PANABIO: A point-referenced pan-Arctic data collection of benthic biotas [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.963640, 2024)
This dataset is a component of the PAN-Arctic data collection of benthic BIOtas (PANABIO) and has been collated during the Census of Marine Life project Arctic Ocean Diversity (ArcOD; http://www.arcodiv.org/). It contains a total of 764 abundance and wet biomass records of 233 macro- and mega-benthic taxa (species to genus level) identified in 18 Agassiz trawl catches and 19 giant box corer samples taken at 37 stations located in the Beaufort Sea at water depths of 71–945 m during one cruise in 2010. The dataset is also available in a PostgreSQL-based data warehouse that can be accessed and queried through an open-access frontend web service at https://critterbase.awi.de/panabio.
Keywords: Abundance; Arctic; Beaufort Sea; Macrobenthos; Wet biomass